Strategies in Empowering Micro, Small, and Medium Enterprises (MSMEs): A Case Study Godhong Ku in the PERKASA Tembesi Program under PT PGN Stasiun Panaran - Dwisda, Khansa; Lausepa, Nabila Zalzabila (Prospect: Jurnal Pemberdayaan Masyarakat, 2025)
The PERKASA (Partnership of Creative, Supportive, and Reliable Communities) Tembesi Program is a Corporate Social Responsibility (CSR) initiative by PT PGN Stasiun Panaran aimed at enhancing the economic capacity of the Tembesi Village community. The program focuses on empowering Micro, Small, and Medium Enterprises (MSMEs), particularly Godhong Ku. Based on Sjaifudin’s grand theory (2015), this study analyzes four dimensions of empowerment: improving financial capability, marketing development, Human Resource development, and management and control strategies. The results of this qualitative descriptive research show that PT PGN Stasiun Panaran does not provide financial assistance in the form of cash, but rather in the form of production facilities and infrastructure (in-kind), which effectively boosts production capacity. In the marketing sector, Godhong Ku successfully combines conventional and digital methods. In human resource development, Godhong Ku actively participates in training that supports the improvement of technical skills. Finally, PGN Stasiun Panaran’s assistance with legal aspects enabled Godhong Ku to obtain a Business Identification Number (NIB) and Trademark Certificate from the Ministry of Law and Human Rights, demonstrating a strengthening of its managerial foundation. Overall, this program proves that an integrated and holistic empowerment strategy is effective in creating competitive and professional MSMEs